TERAPI AKTIVITAS KELOMPOK PENYALURAN ENERGI : SENAM POCO-POCO MENURUNKAN GEJALA PERILAKU KEKERASAN PADA PASIEN SKIZOFRENIA - Ari Dwi Jayanti, Desak Made; Nana Antari, Nyoman (Sport and Fitness Journal; Volume 7, No.1, Januari 2019, 2019)
ABSTRACT Introduction: The main problem that often occurs in schizophrenia patient is violent behavior when can get injure yourself or others. The handling of violent behavior is carried out with a combination of psychopharmacology and psychosocial interventions such as the therapy of channeling group activity. One activity that can be given to reduce violent behavior is through physical activity in the form of dance and motion that is combined with the music of poco-poco gymnastics. The purpose of this study is group activity energy distribusy therapy: poco-poco exercise, decrease symtom of violent behavior on schizophrenic patient. Methods : Type of pre experimental study, using One-group pre-post test design. Sample technique used Purposive sampling with 22 samples. Data collection using observation sheets.Result : The results showed that the risk of pre-test risk behavior was 13.77, including the risk of moderate hardness behavior and post test results of 5.64, including the risk of mild violent behavior. Paired t Test statistic test results obtained p < 0.05 indicates there is group energy distribution therapy activities: poco-poco exercises can decrease symtom of violent behavior in schizophrenic patients. recommended for patients with schizophrenia to be given continuous poco-poco TAK training. Keywords: Poco - Poco Gymnastic, Violent Behavior, Schizophrenic